Pengaruh Penyaluran Zakat Oleh Baznas Terhadap Jumlah Mustahik Miskin Di Kota Jambi Periode 2014-2018 - Eri Riskawati (Pt. Anagata Sembagi Education, 2024)
The purpose of this study was to determine how the development of zakat distribution in BAZNAS and the number of poor mustahik in Jambi city during 2014-2018 and how the influence of zakat distribution by BAZNAS on the number of poor mustahik in Jambi City during 2014-2018. The method used in this research is In this study the authors conducted research with qualitative methods. Qualitative method is a research approach used to understand social phenomena or human behavior from an in-depth and complex perspective. In contrast to quantitative methods that focus more on measuring numbers and statistics, qualitative methods emphasize the collection and analysis of data that is descriptive, contextual, and interpretative. The results showed that there was a significant increase in the receipt and distribution of zakat funds by BAZNAS Jambi City from 2014 to 2018. This shows the efforts of the Jambi City government in increasing the distribution of zakat funds as a way to overcome poverty. The number of poor mustahik who receive zakat from BAZNAS Jambi City has also increased significantly every year. This shows that the increase in the distribution of zakat funds has succeeded in reaching the target population in need.